Как факторы этического лидерства, культуры труда и мотивации государственной службы влияют на неприятие риска государственными служащими и на их организационное гражданское поведение - Акли Зайнал; Уджианто; Сиафи’иАч (Вопросы государственного и муниципального управления, 2019)
The purpose of this study is to analyze the influence of ethical leadership, work culture, and public service motivation on risk aversion and its impact on organizational citizenship behavior. Risk aversion is the prudence of public employees so as not to violate laws and regulations. Risk aversion variable is treated as a consequent variable of ethical leadership, work culture, and motivation based on portfolio theory. The theory sees risk aversion as a contextual behavior, rather than as an individual characteristic. This study was designed with a quantitative descriptive design in a sample of 130 civil servants in the Tapin District Government, South Kalimantan Province, Indonesia. The analysis was carried out by structural equation modeling. The resulting model has a GFI 0.910; CFI 1,000; and RMSEA 0,000. The study found that ethicalleadership has a positive effect on risk aversion but does not have a significant impact on organizational citizenship behavior; work culture has a positive effect on risk aversion and organizational citizenship behavior; public service motivation does not affect risk aversion but has a significant effect on organizational citizenship behavior; and risk aversion has a positive effect on organizational citizenship behavior. This study has implications regarding the importance of the government to develop ethical leadership and a professional work culture in order to encourage the compliance of civil servants in the legislation. This research has a high originality value because it is the first in examining the determinants and antecedents of risk aversion in the context of public employees.